2021
DOI: 10.24191/ajue.v16i4.11947
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneur Education on Business Performance

Abstract: The importance of entrepreneurial role in supporting the country's economic growth has been recognized by experts in the field of entrepreneurship. Today the importance of entrepreneurship has become increasingly important where it has turned into a priority for developing countries including Malaysia. Now, there are many higher educational institutions that are aware of the importance of applying entrepreneurial skills in higher education. Therefore, public universities have to implement entrepreneurship educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…Overall, entrepreneurship education is considered a platform for developing new entrepreneurs (Lajin et al, 2022). According to a study conducted by Mahmood et al (2021) discovers that students are assisted in running their businesses by the university's entrepreneurship curriculum more effectively because of the knowledge and skills they gain (Song et al, 2021). In light of the widely acknowledged importance of entrepreneurship among university students to the advancement of social and economic development, universities and governments are currently considering ways to increase their commitment to these issues (Hassan, 2020).…”
Section: Entrepreneurship Educationmentioning
confidence: 99%
“…Overall, entrepreneurship education is considered a platform for developing new entrepreneurs (Lajin et al, 2022). According to a study conducted by Mahmood et al (2021) discovers that students are assisted in running their businesses by the university's entrepreneurship curriculum more effectively because of the knowledge and skills they gain (Song et al, 2021). In light of the widely acknowledged importance of entrepreneurship among university students to the advancement of social and economic development, universities and governments are currently considering ways to increase their commitment to these issues (Hassan, 2020).…”
Section: Entrepreneurship Educationmentioning
confidence: 99%
“…Becoming an entrepreneur plays a critical role in economic growth. For Mahmood et al (2020), producing students with entrepreneurial skills and competencies will guarantee the success of an entrepreneurial program. Consequently, the course contents should be carefully designed to accommodate the students' needs suited to their program.…”
Section: Weaknessesmentioning
confidence: 99%
“…A study by Bui et al (2020) also shows that among graduates in Vietnam universities who had taken an entrepreneurship course, had shown a greater tendency to become entrepreneurs. Another study by Mahmood, Zahari, Ibrahim, Nik Jaafar and Yaacob (2020) found that entrepreneurship curriculum at the university has facilitated the students in doing their business effectively due to the knowledge and skills learned. There are also researches propose that students have a higher tendency to start their own business after participating in entrepreneurship programmes (Elert, Andersson, & Wennberg, 2015;Olugbola, 2017).…”
Section: Entrepreneurship Education (Ee)mentioning
confidence: 99%